Reconsidering the Date and Provenance of the Book of Hosea: The Case for Persian-Period Yehud. By James M. Bos - Cataldo, Jeremiah W. (The journal of theological studies, 2014)
In the spirit of the now normal trend of hermeneutical suspicion, James Bos draws question to the historical veracity of Hosea—is it really a product of the time period it describes? Or, should one instead date the book of Hosea to the Persian Period despite its superscription pointing to an earlier period, ‘in the days of Kings Uzziah, Jotham, Ahaz, and Hezekiah of Judah, and in the days of King Jeroboam son of Joash of Israel’ (Hos. 1:1)? According to a few scholars it is possible, he points out, to feasibly attribute that superscription to Deuteronomic circles (a point for which he cites only Hans Wolff’s work, Hosea: A Commentary [Philadelphia: Fortress Press, 1974]; cf. p. 138, also n. 23).